The effect of prior eccentric exercise on heavy-intensity cycling: the role of gender and oral contraceptives - Joyce, S.; Sabapathy, S.; Bulmer, A. C.; Minahan, C. (European Journal of Applied Physiology, 2014)
Purpose To determine if gender and/or the use of oral contraceptives alter cycling performance with exercise-induced muscle damage (EiMD). Methods Nine male adults (MEN), nine normally menstruating female adults (WomenNM), and nine female adults using oral contraceptives (WomenOC) participated. Gas exchange and time to exhaustion were measured during continuous cycling performed at three distinct power outputs before (pre) and 48 h after (post) 240 maximal effort eccentric contractions of the quadriceps muscles designed to induce muscle damage (i.e., EiMD). Results The change in muscle damage (i.e., range of motion about the knee joint and serum creatine kinase activity) from pre- compared to post-EiMD was greater in MEN and WomenOC compared to the WomenNM. Time to exhaustion decreased after EiMD in MEN (5.19 ± 4.58 min, p = 0.01) and in WomenOC (2.86 ± 2.83 min, p = 0.02) but did not change in WomenNM (0.98 ± 2.28 min, p = 0.43). Accordingly, the slow component of O2 uptake, expressed relative to time to exhaustion (i.e., %/min), was greater in post- compared to pre-EiMD for MEN (p = 0.02) and the WomenOC (p = 0.03), but not for the WomenNM (p = 0.12). Conclusion The preservation of exercise tolerance during heavy-intensity cycling performed after intense eccentric exercise is improved in women compared to men. Furthermore, the preservation of exercise tolerance is exclusive to 17b-estradiol and cannot be replicated with an exogenous synthetic estrogen replacement delivered in an oral contraceptive.